ON INTUITIONISTIC FUZZY IDEALS BITOPOLOGICAL SPACES (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper  we  introduce  the  notion  of  intuitionistic  fuzzy  ideals in intuitionistic  fuzzy  bitopological  spaces  and  we  prove  some  results  about  it .